Ethical leadership and reputation: Combined indirect effects on organizational deviance - Neves, Pedro (2016)
This is a pre-copyedited, author-produced PDF of an article accepted for publication in Journal of Business Ethics following peer review. The version of record Neves, P., & Story, J. (2015). Ethical Leadership and Reputation: Combined Indirect Effects on Organizational Deviance. Journal of Business Ethics, 127(1), 165–176. “The final publication is available at Springer via http://dx.doi.org/10.1007/s10551-013-1997-3”.